Insect Management for Leafy Vegetables (Lettuce, Endive and Escarole) - Gregg S. Nuessly; Susan E. Webb (EDIS, 2005)
Damage to leafy vegetables results from holes chewed in leaves by caterpillars and beetles, leaf mining by fly larvae and disease transmission and head contamination by piercing sucking insects. Major pests of these crops are beet and southern armyworms, cutworms, cabbage loopers, dipterous leafminers, aphids, cucumber beetles and wireworms. Less common pests of leafy vegetables include seedcorn maggot, seedcorn beetle and corn earworm. This document is ENY-475 (which replaces ENY-430, ENY-432, and ENY-440), one of a series of the Department of Entomology and Nematology, UF/IFAS Extension. Original publication date July 2002. Revised September 2005.